PENGARUH KEMANDIRIAN BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR EKONOMI - Karas, Marsius; Achmadi, Achmadi; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstactThis study aims to determine (1) The Influence of learning Independence to Economic Learning Results of students class X IPS SMAN 4 Pontianak (2) The Influence of Learning Environment on Economic Learning Results of students of class X IPS SMAN 4 Pontianak (3) The Influence of Learning Independence and Learning Environment to the Results of Economic Learning students of class X IPS SMAN 4 Pontianak. The method used descriptive method and the form of research used is the relationship. Population in this research is student of class X IPS SMAN 4 Pontianak which amounted to 133 students which then taken 57 students as sample. Based on the results of the research can be obtained the following results: (1) there is the influence of Independence Learning to Economic Learning Results shown by the value of tcount of 2.535 greater than ttable 1.673 (2,535> 1.673). (2) There is the Influence of Learning Environment on Economic Learning Result shown by the value tcount 2,267 greater than ttable 1,673 (2,267> 1,673). (3) There is Influence of Learning Independence and Learning Environment to Economic Learning Result which shown with coefficient of determination (R2) equal to 0,160. This means that 16% of the Economic Learning Outcomes are explained by the Learning Independence and Learning Environment. While 84% is explained by other factors not examined in this study. Keywords: Learning Independence, Learning Environment, Economic Learning Results